'Opening the door': An authentic approach to decolonizing arts education in Aotearoa/New Zealand. Issue 1 (1st April 2021) - Feast, Luke; Vogels, Christina
Educators in universities in Aotearoa/New Zealand have the responsibility to 'live and model' the principles of Te Tiriti o Waitangi. However, tertiary education has often treated the principles in an inauthentic way. There are few courses in art, design and communication in New Zealand that integrate the principles authentically. This article showcases features of a course ‐ Mahitahi | Collaborative Practices ‐ that engages with Te Tiriti principles by teaching collaboration from te ao Māori (the Māori world). Our findings draw from a focus group we conducted with academic staff who taught into a pilot iteration of the course. Three central themes emerged from the focus group relating to the issue of decolonizing arts education. First, that regardless of the educators' intentions to design a course that privileges te ao Māori, the features of Aotearoa/New Zealand's colonial reality are still present. Second, the students' primary learning activity was principled reflection, where they successfully engaged with te ao Māori in an authentic way. Third, students' connection to te ao Māori was jeopardized by designing part of the assessment that took on a Pākehā (non-Māori) world-view. Consequently, students may have missed the opportunity to engage more fully with educative experiences relating to lifelong learning. We argue that to maintain an authentic connection to te ao Māori, the curriculum should be consistently designed around principles embedded in Te Tiriti o Waitangi.